2014
DOI: 10.1603/me14015
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Annual Changes in Abundance ofAedes(Stegomyia)aegyptiandAedes(Ochlerotatus)epactius(Diptera: Culicidae) in High-Elevation Communities in México

Abstract: We examined temporal changes in the abundance of the mosquitoes Aedes (Stegomyia) aegypti (L.) and Aedes (Ochlerotatus) epactius Dyar & Knab from June to October 2012 in one reference community at lower elevation (Rio Blanco; approximately 1,270 m) and three high-elevation communities (Acultzingo, Maltrata, and Puebla City; 1,670-2,150 m) in Veracruz and Puebla States, México. The combination of surveys for pupae in water-filled containers and trapping of adults, using BG-Sentinel traps baited with the BG-Lure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…aegypti is highly abundant, to the high elevation Puebla City at ~2100 m, where Ae. aegypti is rarely found (Lozano-Fuentes et al 2012, 2014). We found that our energy balance modeling approach adds an important level of complexity and nonlinearity to water temperature variability, leading to results that are not always intuitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti is highly abundant, to the high elevation Puebla City at ~2100 m, where Ae. aegypti is rarely found (Lozano-Fuentes et al 2012, 2014). We found that our energy balance modeling approach adds an important level of complexity and nonlinearity to water temperature variability, leading to results that are not always intuitive.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti immatures in containers in 12 communities located along an elevation and climate gradient in central México (Lozano-Fuentes et al 2012, 2014). Three representative communities along this gradient are Veracruz City at sea level, with highly favorable climatic conditions for the mosquito; Rio Blanco along the eastern slopes of the Sierra Madre Oriental (~1250 m), where the mosquito is moderately abundant; and Puebla City in the central highlands (~2100 m), where a few specimens of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…However, the most recent survey indicated the intermittent presence of S. aegypti at 2130 m a.s.l. in Puebla State (Lozano‐Fuentes et al ., , ). Consequently, Mexican control programmes have adopted monitoring and surveillance schemes in localities in which the presence of the mosquito is unlikely, such as in Mexico City.…”
mentioning
confidence: 99%
“…Recently, populations of S. aegypti in Mexico have been reported much more frequently in localities with dry and cold conditions (Lozano-Fuentes et al, 2014). Historically, this mosquito species has been well established in regions located below 1700 m a.s.l.…”
mentioning
confidence: 99%